2022
DOI: 10.3390/su141710539
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Self-Identity on Perceived Image, Warm Glow and Willingness to Purchase: A New Generation’s Perspective towards Eco-Friendly Restaurants

Abstract: Compared to other generations, Generation Z (Gen Z) tend to be more concerned with environmental problems, prefer healthier food options, and are willing to pay premium prices for eco-friendly food products. Until now, however, this market segment had not been the focus of any sustainability research in the restaurant context. The present study fills this gap while exploring if green self-identity (one’s alignment with environmental concerns) influences perceptions of green restaurants (one’s perceived image o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The role of the warm glow feeling diverse technologies and are savvy enough to find information, carefully evaluate options in relation to their interests and make donations. Such groups are also quite interested in the issues of social responsibility, questioning social conditions and arguing with awareness of current social problems (Mahasuweerachai and Suttikun, 2022). Thus, individualism and selfconfidence in the young generation may contribute to the weak effects of family and close friends on their feeling of happiness from participating in a charity run.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the warm glow feeling diverse technologies and are savvy enough to find information, carefully evaluate options in relation to their interests and make donations. Such groups are also quite interested in the issues of social responsibility, questioning social conditions and arguing with awareness of current social problems (Mahasuweerachai and Suttikun, 2022). Thus, individualism and selfconfidence in the young generation may contribute to the weak effects of family and close friends on their feeling of happiness from participating in a charity run.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…The role of the warm glow feeling through identity signals aids in predicting individuals' future behaviour (Mahasuweerachai and Suttikun, 2022;Wood et al, 2010). Therefore, the warm glow of giving theory is used in the present study to explain the relationships between perceptions of charity sporting events and the feeling of a warm glow leading to enjoyment and willingness to return to charity sports events.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sun and Wang (2020) found that consumers who recognize the environmental benefits of green products are inclined to support businesses that offer these products by making purchases. Despite limited research on the connections between sustainable restaurant image, warm glow, perceived sustainability value, and willingness to pay a premium, Mahasuweerachai and Suttikun (2022) found that young consumers associating a green image with warm glow are more inclined to visit eco‐friendly restaurants. Our study builds on this, showing that those experiencing warm glow at sustainability‐promoting restaurants perceive greater value in their purchases, influencing a higher willingness to pay premium prices.…”
Section: Discussionmentioning
confidence: 99%
“…Green self-identity, which is an issue that individuals with high environmental awareness attach importance, is evaluated in relation to recycling and sustainability issues. Individuals, as consumers, can shape their consumption habits in this direction if their green self-identity awareness is high [ 55 ].…”
Section: Conceptional Frameworkmentioning
confidence: 99%